Literasi Keuangan Syariah Tentang Produk Derivatif Pasar Modal Syariah - Yetti Afrida Indra; Vahmi Basuki (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
This study is to determine the level of Islamic financial literacy of Islamic banking study program students about Islamic capital market derivative products. The data used in this study are primary data obtained from questionnaires distributed to respondents. The instrument used was a closed questionnaire with a Likert scale. The sample in this study amounted to 70 students of Islamic banking study programs in the year 2015/2016. Data analysis techniques in the validity test using Person Correlation, reliability testing using Cronbach Alpha and frequency testing. The results showed that the level of Islamic financial literacy of IAIN Bengkulu Islamic study program students was in the Medium category. The medium category is in the indicators of the level of knowledge and confidence level of 62.88% and 62.91%. Whereas the skill level indicator was 57.74% or still low. This percentage is interpreted into financial literacy level criteria according to Chen & Volpe, which are low (<60%) and moderate categories (60 ≤ 79%).